Students of Šiauliai University of Applied Sciences associate their future with medicine - Korsakaitė, Domantė; Lobeiko, Rasa; Matelionytė, Karolina (Slauga. Mokslas ir praktika, 2020)
Expectations of Šiauliai College students.